2013
DOI: 10.1002/ajhb.22359
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in BMI and adiposity rebound among girls from Kraków (Poland) over the last 30 years (from 1983 to 2010)

Abstract: AR cannot be explained only by changes in body adiposity. Early AR could be a marker of acceleration of development already in an early postnatal ontogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(57 reference statements)
3
13
0
1
Order By: Relevance
“…1,15,16 Early AR reflects excessive positive energy balance in early life 2,5,24,25 ; therefore, influencing health behaviors (eg, toddlers' lifestyles) before the AR has occurred may reduce the risk of early AR and its sequelae. Our findings, together with evidence indicating that the AR occurs earlier n o wt h a ni nt h ep a s t , 2,5,25,27,28 provide a justification to policy makers and clinical practitioners to consider (1) more populationwide public health interventions in early childhood to delay timing of AR, (2) increased growth monitoring in early childhood to identify children at risk of early AR (eg, those with obese parents) or those who experienced early AR and are therefore in greatest need of preventive efforts, and (3) more clinical interventions directed at these "high risk" children and their families.…”
Section: E1358supporting
confidence: 79%
“…1,15,16 Early AR reflects excessive positive energy balance in early life 2,5,24,25 ; therefore, influencing health behaviors (eg, toddlers' lifestyles) before the AR has occurred may reduce the risk of early AR and its sequelae. Our findings, together with evidence indicating that the AR occurs earlier n o wt h a ni nt h ep a s t , 2,5,25,27,28 provide a justification to policy makers and clinical practitioners to consider (1) more populationwide public health interventions in early childhood to delay timing of AR, (2) increased growth monitoring in early childhood to identify children at risk of early AR (eg, those with obese parents) or those who experienced early AR and are therefore in greatest need of preventive efforts, and (3) more clinical interventions directed at these "high risk" children and their families.…”
Section: E1358supporting
confidence: 79%
“…1,15,16 Early AR reflects excessive positive energy balance in early life 2,5,24,25 ; therefore, influencing health behaviors (eg, toddlers' lifestyles) before the AR has occurred may reduce the risk of early AR and its sequelae. Our findings, together with evidence indicating that the AR occurs earlier now than in the past, 2,5,25,27,28 provide a justification to policy makers and clinical practitioners to consider (1) more populationwide public health interventions in early childhood to delay timing of AR, (2) increased growth monitoring in early childhood to identify children at risk of early AR (eg, those with obese parents) or those who experienced early AR and are therefore in greatest need of preventive efforts, and (3) more clinical interventions directed at these "high risk" children and their families.…”
Section: Figuresupporting
confidence: 76%
“…Considering that we had insufficient frequency of measured data in this study, the median timing of AR would be between 3.8 years (Exam-V) and 4.8 years (Exam-VI) of age, regardless of birth weight and sex. This is about one year earlier than that seen in the Korean standards, which may coincide with the global shifts in AR timing to an earlier age [12,[17][18][19]. The most recent survey conducted in Poland in 2010 showed AR timing of subjects (with median BMIs) as 5.2 years in boys and 3.0 years in girls, which was 2.3-4.4 years earlier than the values obtained in 1983 [17,18].…”
Section: Discussionmentioning
confidence: 63%
“…Currently, beyond the role of predicting obesity, earlier AR over time may imply the acceleration of growth and development compared to the past. Based on a longitudinal study, shifting of AR timing was observed not only for children with normal weight, overweight, and obesity, but also in underweight children [12,17,18]. Unfortunately, minimum BMI in underweight subjects of the 5 th percentile was not confirmed during this period, because follow-up period (69 months) was short to confirm AR timing of all subjects in this study.…”
Section: Discussionmentioning
confidence: 67%